As Fileiras Baseadas na Floresta: Análise Sectorial - Louro, Graça; Rego, Francisco; Monteiro, Maria; Machado, Henrique (Silva Lusitana, 2013)
In this study we highlight the importance of Portuguese forests based chains in relation to the theory of ecosystem services. Moreover, we characterize the chains of wood and wooden furniture, of pulp paper and paperboard and of cork, in terms of their productive structure, production flows and markets. We point out as well the renewed interest in resin products and respective chain. We also consider as macroeconomic relevant, both at regional and national level, the economic activities based on chestnuts and pine nuts which only recently are regarded as integrated chains, from raw material up to the end product. In addition, we analyse the biomass for energy according to the new context of this chain, associated to the mitigation of climate change and to the reducing of wildfire risk. We underline as well other services/products of forest ecosystems for their importance in a sector analysis approach, namely the ones associated to holm oak, carbon economy and nature conservation. We also refer the macroeconomic relevance of the forest sector in terms of national balance sheet, international markets and job creation.
Keywords: Cork; forest biomass; forest chains; market; Wood

Biomass, nutrient content, litterfall and nutrient return to the soil in Mediterranean oak forests - Rapp, Maurice; Santa Regina, Ignacio; Rico, Mercedes; Gallego, Humberto Antonio (Forest Ecology and Management, 1999)
We estimated above-ground biomass, nutrient content, litterfall and nutrient return to the soil in deciduous and evergreen Quercus pyrenaica Will., Quercus lanuginosa Lamk and evergreen Quercus ilex L. oak forests, respectively, near Salamanca (Spain) and Montpellier (France). The calculated biomass ranged from 64 to 121 Mg ha ÿ1 . Perennial material (trunks and branches) represented 96±97% in the four Spanish Q. pyrenaica stands and 93% in the French Q. lanuginosa and Q. ilex stands. Q. pyrenaica had higher P, Mg, Fe and Mn contents than the other two species from southern France. In contrast, these latter species had higher N and Ca concentrations. All of these differences were related to soil nutrient availability, especially Ca, Mg, P, Fe and Mn. Comparison of the chemical composition of leaves on trees with that of leaf litter indicated retention and translocation of N, P and K from leaves to perennial biomass and recycling of Ca and Mg from trees to the soil
Keywords: forest biomass; forest ecosystems; litterfall; Q. ilex; Q. lanuginosa; Q. pyrenaica

Biomass, nutrient content, litterfall and nutrient return to the soil in Mediterranean oak forests - Rapp, Maurice; Santa Regina, Ignacio; Rico, Mercedes; Gallego, Humberto Antonio (Forest Ecology and Management, 1999)
We estimated above-ground biomass, nutrient content, litterfall and nutrient return to the soil in deciduous and evergreen Quercus pyrenaica Will., Quercus lanuginosa Lamk and evergreen Quercus ilex L. oak forests, respectively, near Salamanca (Spain) and Montpellier (France). The calculated biomass ranged from 64 to 121 Mg ha ÿ1 . Perennial material (trunks and branches) represented 96±97% in the four Spanish Q. pyrenaica stands and 93% in the French Q. lanuginosa and Q. ilex stands. Q. pyrenaica had higher P, Mg, Fe and Mn contents than the other two species from southern France. In contrast, these latter species had higher N and Ca concentrations. All of these differences were related to soil nutrient availability, especially Ca, Mg, P, Fe and Mn. Comparison of the chemical composition of leaves on trees with that of leaf litter indicated retention and translocation of N, P and K from leaves to perennial biomass and recycling of Ca and Mg from trees to the soil
Keywords: forest biomass; forest ecosystems; litterfall; Q. ilex; Q. lanuginosa; Q. pyrenaica